2016
DOI: 10.1016/j.apmr.2016.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Versus Laboratory-Based Robotic Ankle Training for Children With Cerebral Palsy: A Pilot Randomized Comparative Trial

Abstract: These findings suggest that the translation of repetitive, goal-directed, biofeedback training through motivating games from the laboratory to the home environment is feasible. The benefits of home-based robot-guided therapy were similar to those of laboratory-based robot-guided therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 50 publications
0
35
0
3
Order By: Relevance
“…It was found that VR game training with teleassistance is not only convenient and economical but also effective based on significant improvement in passive and active joint ROM, muscle strength, spasticity, and balance after the training at home. Chen et al [ 14 ] divided 41 children with CP to a laboratory-based group and a home-based group to conduct the same VR game training. This also suggested that VR game training is feasible to be conducted at home since both groups received similar benefits after the training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that VR game training with teleassistance is not only convenient and economical but also effective based on significant improvement in passive and active joint ROM, muscle strength, spasticity, and balance after the training at home. Chen et al [ 14 ] divided 41 children with CP to a laboratory-based group and a home-based group to conduct the same VR game training. This also suggested that VR game training is feasible to be conducted at home since both groups received similar benefits after the training.…”
Section: Discussionmentioning
confidence: 99%
“…When conducting intelligent passive stretching, subjects are requested to feel relaxed with ankle joints being stretched to follow up predefined motion trajectories of the robot and without resistance force generated from their ankle joints [ 22 ]. In the clinical research, intelligent passive stretching is usually regarded as either a process of warming up to energize impaired ankle joints or a process of cooling down to eliminate the tension of ankle joints at the end of the training [ 14 , 49 , 53 , 59 , 65 ]. In general, intelligent passive stretching can avoid accidental injuries to ankle joints, because of its inverse proportion between the rotating speed and the resistance torque of ankle joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insufficient provision of therapeutic services for children with disabilities is an internationally recognized problem. Therefore, alternative service delivery models have been proposed, including family‐centred and domiciliary approaches . However, such home‐based approaches present relevant limitations as clinicians are not allowed to manage ongoing treatment directly to verify compliance and adherence.…”
mentioning
confidence: 99%
“…Therefore, alternative service delivery models have been proposed, including family-centred and domiciliary approaches. [10][11][12][13][14] However, such home-based approaches present relevant limitations as clinicians are not allowed to manage ongoing treatment directly to verify compliance and adherence.…”
mentioning
confidence: 99%